When to perform a pancreatoduodenectomy in the absence of positive histology?: a consensus statement by the International Study Group of Pancreatic Surgery - Asbun, Horacio J.; Conlon, Kevin; Fernandez-Cruz, Laureano; Friess, Helmut; Shrikhande, Shailesh V.; Adham, Mustapha; Bassi, Claudio; Bockhorn, Maximilian; Büchler, Markus W.; Charnley, Richard M.; Dervenis, Christos; Fingerhutt, Abe; et al. (Surgery, 2014)
Background - Pancreatoduodenectomy (PD) provides the best chance for cure in the treatment of patients with localized pancreatic head cancer. In patients with a suspected, clinically resectable pancreatic head malignancy, the need for histologic confirmation before proceeding with PD has not historically been required, but remains controversial. - Methods - An international panel of pancreatic surgeons working in well-known, high-volume centers reviewed the literature and worked together to establish a consensus on when to perform a PD in the absence of positive histology. - Results - The incidence of benign disease after PD for a presumed malignancy is 5-13%. Diagnosis by endoscopic cholangiopancreatography brushings and percutaneous fine-needle aspiration are highly specific, but poorly sensitive. Aspiration biopsy guided by endoscopic ultrasonography (EUS) has greater sensitivity, but it is highly operator dependent and increases expense. The incidence of autoimmune pancreatitis (AIP) in the benign resected specimens is 30-43%. EUS-guided Trucut biopsy, serum levels of immunoglobulin G4, and HISORt (Histology, Imaging, Serology, Other organ involvement, and Response to therapy) are used for diagnosis. If AIP is suspected but not confirmed, the response to a short course of steroids is helpful for diagnosis. - Conclusion - In the presence of a solid mass suspicious for malignancy, consensus was reached that biopsy proof is not required before proceeding with resection. Confirmation of malignancy, however, is mandatory for patients with borderline resectable disease to be treated with neoadjuvant therapy before exploration for resection. When a diagnosis of AIP is highly suspected, a biopsy is recommended, and a short course of steroid treatment should be considered if the biopsy does not reveal features suspicious for malignancy.
Gesehen am 08.09.2020